Data Collection Unit – A Platform for Printing Process Authentication - Gillich, Eugen; Hoffmann, Jan Leif; Dörksen, Helene; Lohweg, Volker; Schaede, Johannes (Optical Document Security - The Conference on Optical Security and Counterfeit Detection V)
Banknote authentication plays a fundamental role in banknote circulation. Banknotes undergo some major changes in thenext years because electronic payment systems will get more common which will change the user behaviour. Furthermore,technologies of counterfeiters will improve progressively and continuously. We propose a two-sage procedure for theeffective development for the design of simple electronics for cash handliung systems: First, we establish a high qualityimage acquisition system which allows for a consistent image capture quality and is able to handle complex softwarealgorithms for banknote authentication. Second, we take the algorithms and port them on cost-efficient hardware. It isshown in this paper that a reliable authentication of almost each banknote is possible for to specialised low-cost systemssuch as point-of-sale cash units.